Confusing the drug facts on one nonprescription drug label with those on another: The Drug Facts Label as a text schema. Issue 1 (6th April 2016) - Ryan, Michael P; Costello-White, Reagan N; Sandoval, Mercedes N
The Drug Facts Label is designed to guide consumers in comparing nonprescription drugs. Undergraduates studied and recalled drug facts for three analgesic or non-analgesic labels using Drug Facts Label headings as retrieval cues. They then studied and recalled drug facts from an aspirin label. Aspirin recall was greater when the prior labels were analgesics, but prior-label intrusion errors were also greater. These two effects were associated with the number of prior drug labels on which facilitating and interfering drug facts appeared. Using the Drug Facts Label schema to read drug labels can both enhance and degrade the recall of nonprescription drug facts.